Histoenzymic distribution of phosphatases and oxidoreductases in testes of donkeys - UPPAL, VARINDER; BANSAL, NELAM; ROY, K S (The Indian Journal of Animal Sciences, 2014)
Histoenzymic localization of phosphatases and oxidoreductases was studied on the testes of 4 adults donkeys. The cryoslal sections of 10 Âµm were incubated fbr demonstration of alkaline (AKPase) and acid (ACPase) phosphatases, adenosine triphosphatase (ATPase), glucose -6- phosphatase (G-6-Pase), succinate dehydrogenase (SDH), lactate dehydrogenase (LDH), reduced nicotinamide adenine dinucleotide phosphatase (NADPH), 17-Î²-hydroxysteriod dehydrogenase (17-Î²-HSD), glucose -6-phosphatase dehydrogenase (G-6-PD), monoamine oxidase (MAO) and nonspecifices (erases (NSE). The distribution pattem of above enzymes was studies in tne seminiferous tubules, interlobular stroma and leydig cells and discussed.